Influence Of Different Levels Of Energy On Growth Performance Of Crossbred Pigs - Rekha P (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2001)
An experiment was conducted to assess •the influence of different levels of energy on the growth performance of crossbred (Large White Yorkshire x Desi) pigs. Fifteen male (castrated) and fifteen female weaned crossbred piglets with an average body weight of 12.9 kg were divided into three equal groups as uniformly as possible with regard to age, sex and body weight. The three groups of piglets were maintained on three rations with 16 per cent crude protein but differing in their energy content, viz., 2800 kcal (T1), 3000 kcal CT2) and 3200 kcal (TI) of digestible energy (DE) per kg. The average daily gains recorded for the three groups T1, T2 and TI were 262.9, 302.0 and 362.8 g respectively. The cumulative feed conversion efficiencies were 6.0, 5.2 and 4.1 for the groups T1, T2 and TI respectively. The values recorded for TI were higher (P<0.01) than those for T1 and T2. The digestibility coefficients of nutrients except that of crude fibre and crude protein were found to improve with increase in the energy content of the rations. Study of the carcass traits revealed that the body weight at slaughter and dressed weight without head improved as the energy content of the rations